Market Efficiency Based on Unconventional Technical Trading Strategies in Malaysian Stock Market - Soon, Ling Pick; Abdul-Rahim, Ruzita (International Journal of Economics and Financial Issues, 2017)
This study examines the efficiency of Malaysian stock market based on the effectiveness of unconventional technical trading strategies which combine buy recommendation of securities experts with sell signals from 10 different technical strategies (SMA, MAE, Bollinger bands, momentum, commodity channel index, relative strength index, stochastic, Williams percentage range, MACD oscillator and shooting star). We collect 1,665 buy recommendations involving 173 shares over a 3-year period starting January 1, 2013 until December 31, 2015. To ensure each buy recommendation is matched with the technical strategy’s sell signals, the period is extended until March 31, 2016. Results of Jensen’s alpha show that 6 out of 10 technical trading rules are significant in generating risk-adjusted net abnormal returns, suggesting Malaysian stock market is still inefficient in the weak form. This conclusion is supported with results of unit root tests on daily returns of the 173 shares over the same study period. Keywords: Stock market efficiency, technical trading strategy, Malaysian stock market JEL Classifications: L11, O16, P45